.25g+6=12

Simple and best practice solution for .25g+6=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .25g+6=12 equation:


Simplifying
0.25g + 6 = 12

Reorder the terms:
6 + 0.25g = 12

Solving
6 + 0.25g = 12

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 0.25g = 12 + -6

Combine like terms: 6 + -6 = 0
0 + 0.25g = 12 + -6
0.25g = 12 + -6

Combine like terms: 12 + -6 = 6
0.25g = 6

Divide each side by '0.25'.
g = 24

Simplifying
g = 24

See similar equations:

| x^2+2x+2=y | | 3x+9+7x=31 | | -2n+7=-19 | | 14/7+3 | | 28-(3c+4)=2(c+12)+c | | (x+10)=(x+2) | | 2x^3-50x^2-50x+1235=0 | | -2x-6=x+15 | | 2x-14=x+2 | | 2x^3-50x^2-50x+1250=0 | | (2x+4)/3=(x/6)-(3) | | 5f+6f=126 | | d/6+12=19 | | (2x+4)/3=x/6-(3) | | 2(5m+3m)-4(3m-3)=m(m-8)-m(m+7) | | 1.7x-x=210 | | 45k-8=15k+382 | | x+6=x-3(x+6) | | (x)/5+(x)/3-(1)=x/2 | | 2(5m+3)-4(3m-3)=m(m-8)-m(m+7) | | (2x-5)/12=(-x)/4-(5)/3 | | 3x-x=600 | | -1.4(x+2)=4.2 | | 1/2(y-18)=-2 | | (x+6)x(x-9)=6 | | 10i+3=20-i+82 | | 4x-4/x-7*3x+5/x-1 | | 13w+2=5w-6 | | (1)/(2x-8)+1/(x-4) | | 3/2(x-4) | | 8m+20=3m-5 | | -t^2+13t=0 |

Equations solver categories